(untitled) (Polis (Santiago), 2018)
In the United Nations discourse on sustainable development it is possible to identify the linguistic-discursive strategies and resources that constitutes the social representation of persons and populations that are named “poor”. Thus, in this paper we show the operation of the implicit discursive as one of these strategies. Also, through this social representation an identity of a global reach is attributed to this persons and populations; therefore, we incorporate the implication of the contextual determinants both on the discursive realization of this development model as on the processes of social representation. As well, the epistemological references that guide this study correspond to the premises about the use of language, both on the theory of social representations as that of discourse studies.